Design of Hospital Inpatient Unit Using the Evidence-Based Design (EBD) Approach - Marison, Artian Ferry; Tela, I Nengah; Wongso, Jonny (Jurnal Arsitektur, 2025)
The design of inpatient rooms significantly influences patient comfort and hospitalization experiences. This study analyzes the impact of inpatient room design elements on patient experience based on Supportive Design Theory and evaluates the Evidence-Based Design (EBD) implementation at Santa Maria Hospital, Pekanbaru. A mixed-method strategy using Concurrent Triangulation Design was employed, integrating quantitative and qualitative analyses simultaneously. Quantitative data from questionnaires of 46 recovered patients were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. Findings indicate that physical room aspects significantly influenced perceived control (β=0.684; p=0.000), social support (β=0.391; p=0.001), positive distraction (β=0.546; p=0.000), and overall patient experience (β=0.370; p=0.013). Qualitative analysis using NVivo highlighted natural lighting, privacy curtains, and ergonomic furniture as key factors enhancing patient satisfaction. The study provides evidence-based design criteria for Class III inpatient rooms and introduces scientific novelty by simultaneously integrating PLS-SEM and NVivo methods, rarely applied in Indonesian hospital contexts, especially in standard-class inpatient facilities.